Rational Design of Biosafety Level 2-Approved, Multidrug-Resistant Strains of Mycobacterium tuberculosis through Nutrient Auxotrophy - Catherine Vilchèze (American Society for Microbiology, 2018)
ABSTRACT Multidrug-resistant (MDR) tuberculosis, defined as tuberculosis resistant to the two first-line drugs isoniazid and rifampin, poses a serious problem for global tuberculosis control strategies. Lack of a safe and convenient model organism hampers progress in combating the spread of MDR strains of Mycobacterium tuberculosis. We reasoned that auxotrophic MDR mutants of M. tuberculosis would provide a safe means for studying MDR M. tuberculosis without the need for a biosafety level 3 (BSL3) laboratory. Two different sets of triple auxotrophic mutants of M. tuberculosis were generated, which were auxotrophic for the nutrients leucine, pantothenate, and arginine or for leucine, pantothenate, and methionine. These triple auxotrophic strains retained their acid-fastness, their ability to generate both a drug persistence phenotype and drug-resistant mutants, and their susceptibility to plaque-forming mycobacterial phages. MDR triple auxotrophic mutants were obtained in a two-step fashion, selecting first for solely isoniazid-resistant or rifampin-resistant mutants. Interestingly, selection for isoniazid-resistant mutants of the methionine auxotroph generated isolates with single point mutations in katG, which encodes an isoniazid-activating enzyme, whereas similar selection using the arginine auxotroph yielded isoniazid-resistant mutants with large deletions in the chromosomal region containing katG. These M. tuberculosis MDR strains were readily sterilized by second-line tuberculosis drugs and failed to kill immunocompromised mice. These strains provide attractive candidates for M. tuberculosis biology studies and drug screening outside the BSL3 facility. IMPORTANCE Elimination of Mycobacterium tuberculosis, the bacterium causing tuberculosis, requires enhanced understanding of its biology in order to identify new drugs against drug-susceptible and drug-resistant M. tuberculosis as well as uncovering novel pathways that lead to M. tuberculosis death. To circumvent the need for a biosafety level 3 (BSL3) laboratory when conducting research on M. tuberculosis, we have generated drug-susceptible and drug-resistant triple auxotrophic strains of M. tuberculosis suitable for use in a BSL2 laboratory. These strains originate from a double auxotrophic M. tuberculosis strain, H37Rv ΔpanCD ΔleuCD, which was reclassified as a BSL2 strain based on its lack of lethality in immunocompromised and immunocompetent mice. A third auxotrophy (methionine or arginine) was introduced via deletion of metA or argB, respectively, since M. tuberculosis ΔmetA and M. tuberculosis ΔargB are unable to survive amino acid auxotrophy and infect their host. The resulting triple auxotrophic M. tuberculosis strains retained characteristics of M. tuberculosis relevant for most types of investigations.